Kidah-kidahan Tradition: Neglect of Child Welfare in Forced Engagement in South Sumatera - Barkah, Qodariah; Rismawati, Shinta Dewi; Abdillah, Muhammad; Saputra, Jemmi Angga; Fernando, Henky (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Local traditions have become a source of legitimacy for the practice of forced arranged marriages that has been passed down from generation to generation. Underage children (below 19 years old) have been forced into arranged marriages as an economic solution for the family. This paper aims to analyze how the arranged marriage tradition takes place and what is the position of minors in this tradition. How the actions of parents to force their children to accept arranged marriages have bad consequences for children's social welfare. At the same time, how do local traditions justify actions that ignore the interests of children to be able to live according to their rights as children. The data for this paper are based on a qualitative study by observing forced marriage practices in a subdistrict in the South Sumatera region. A series of interviews were conducted both with children who experienced forced marriages, as well as with the parents and traditional figures involved. The research results show two important things. First, that forced marriages occur as a family strategy to get out of economic pressure by shifting the burden of responsibility on the prospective husband's family. Second, the practice of forced matchmaking that takes place on children has changed the life orientation of children and threatens their social welfare. This research emphasizes the need for legal protection for children's rights so that children's welfare can be guaranteed.